2022
DOI: 10.3847/1538-4357/ac46d3
|View full text |Cite
|
Sign up to set email alerts
|

S 5: The Orbital and Chemical Properties of One Dozen Stellar Streams

Abstract: We report the kinematic, orbital, and chemical properties of 12 stellar streams with no evident progenitors using line-of-sight velocities and metallicities from the Southern Stellar Stream Spectroscopic Survey (S 5), proper motions from Gaia EDR3, and distances derived from distance tracers or the literature. This data set provides the largest homogeneously analyzed set of streams with full 6D kinematics and metallicities. All streams have heliocentric distances between ∼10 and 50 kpc. The v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
76
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 136 publications
17
76
0
Order By: Relevance
“…The Southern Stellar Stream Spectroscopy Survey (S5; Li et al 2019) reported observations of 25 Palca members in the field of the ATLAS-Aliqa-Uma (AAU) stream (Li et al 2021), which overlaps Palca on the sky but with a perpendicular stream track. Most of the Palca members near AAU have kinematics consistent with the Cetus model (Li et al 2022), as will be shown in detail in this study. This confirmation encourages us to search for more Cetus-Palca members in the southern sky.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…The Southern Stellar Stream Spectroscopy Survey (S5; Li et al 2019) reported observations of 25 Palca members in the field of the ATLAS-Aliqa-Uma (AAU) stream (Li et al 2021), which overlaps Palca on the sky but with a perpendicular stream track. Most of the Palca members near AAU have kinematics consistent with the Cetus model (Li et al 2022), as will be shown in detail in this study. This confirmation encourages us to search for more Cetus-Palca members in the southern sky.…”
Section: Introductionsupporting
confidence: 69%
“…The Palca stream has a fairly large width, and extends over 60°, almost reaching the edge of the DES survey at δ = −60°. The potential connection between the Palca and Cetus streams was already discussed by Chang et al (2020) and Li et al (2022). Using the 24 Palca members with radial velocity measurements from S5 (cyan diamonds in Figure 3) in the field of AAU (Li et al 2021), we apply the technique described in Section 4.1 to quantify the confidence of their association.…”
Section: Palca and Atlas-aliqa Uma And Eridanus-phoenixmentioning
confidence: 96%
See 3 more Smart Citations